The Philosophical Roots of the Philosophy of Rights - Al-Qaisi, Eman; Shomar, Towfic (Jordan Journal of Social Sciences, 2023)
Georg Wilhelm Hegel’s book Elements of the Philosophy of Right and the discussions of his work initiated modern perception of the philosophy of rights, support, and critique. Many studies focused on the concept of rights, especially natural and divine rights. Still, research on the roots of the philosophy of rights remains interesting. Accordingly, this research examines the concept of rights to understand the beginnings that heralded modern and contemporary philosophical positions, starting with Greek philosophy and all the way to the dawn of modern philosophy. The study aims to examine the philosophical origins and schools of philosophy on the issue of rights by tracing the gradual development of this concept, starting with Greek philosophy, through the Middle Ages and ending with Descartes. It aims to reveal the role played by these philosophical schools in developing the concept of rights within their various natural, social, and political frameworks. The research also reviews the works of the most prominent philosophers of the period. The problem at the heart of the research lies in the crucial questions it raises about the concept of rights, its origins and features and in showcasing the main differences among the philosophical schools regarding such a concept. These questions are: What are rights? What are the philosophical schools of thought on which this concept is based, and how did these contribute to its development? The research adopts the historical-analytical method, with the aim of providing a historical vision of the concept of rights and its predicaments. The historical review of philosophical positions reveals that the concept of rights had its origins in ancient and medieval philosophy, which had not been combined as an independent unit of philosophy; rather, it was a combination of the relationship among concepts of rights, duties, justice, and freedom. Therefore, Hegel’s description of the history of philosophy as evolutionary is valid since it is continuous, structural, and evolving in nature. The foundations of the concept of rights did not originate with Hegel, as these were natural and appropriate developments of the relationship of the idea and its opposite within a historical process that led to Hegel’s views extrapolated in his book “Elements of the Philosophy of Right”.